Identification System for Different Punjabi Dialects Using Random Forest Technique - Singh, Ravinder; Sharma, Anand (International Journal of Computer Sciences and Engineering, 2018)
In modern era of technology every one relies on technology. From start of day to end of day humans depends on machines and machines need input signal for performing tasks. Many systems have been developed which works on native language input speech. Punjabi is also one of them, there are many speeches and dialect recognition systems are available but all have some common problems like problem with different dialects words of Punjabi is main one. In Punjabi language Majha, Malwa, Doaba are main dialect in eastern Punjab, most of time words from Majha dialect is similar to Taksali Punjabi but when we talk in Doaba and most populated dialect Malwa it is difficult for speech recognition system to understand that word and perform tasks so that was whey dialect identification system is need of hour. The aim of this paper is discuss about new proposed algorithm by authors which works on Punjabi dialects and to compare with previous algorithms with respect to accuracy.